Endoscopic Ultrasound-Guided Versus Percutaneous Transhepatic Biliary Drainage in Patients With Malignant Biliary Obstruction: Which Is the Optimal Cost-Saving Strategy After Failed ERCP? - Yoon, Won Jae; Shah, Eric D.; Lee, Tae Hoon; Jang, Sunguk; Law, Ryan; Park, Do Hyun (Frontiers in Oncology, 2022)
Background and Aim Although endoscopic ultrasound-guided biliary drainage (EUS-BD) after failed primary ERCP in malignant distal biliary obstruction has similar clinical outcomes compared to percutaneous transhepatic biliary drainage (PTBD), little is known about optimal cost-saving strategy after failed ERCP. We performed a cost analysis of EUS-BD and PTBD after failed ERCP in two countries with different health care systems in the East and West. Methods From an unpublished database nested in a randomized controlled trial, we compared the cost between EUS-BD and PTBD in Korea. The total cost was defined as the sum of the total biliary drainage costs plus the cost of hospital stay to manage adverse events. We also performed a cost-minimization analysis using a decision-analytic model of a US Medicare population. Results In Korea, the median total costs for the biliary intervention (1,203.36 for EUS-BD vs. 1,517.83 for PTBD; P=.0015) and the median total costs for the entire treatment were significantly higher in PTBD (4,175.53 for EUS-BD vs. 5,391.87 for PTBD; P=.0496) due to higher re-intervention rate in PTBD. In cost-minimization analysis of US Medicare population, EUS-BD would cost 9,497.03 and PTBD 13,878.44 from a Medicare insurance perspective (average cost-savings in choosing EUS-BD of 4,381.41 in the US). In sensitivity analysis, EUS-BD was favored over PTBD regardless of the expected re-intervention rate in EUS-BD and PTBD. Conclusions EUS-BD may have an impact on cost-savings due to better clinical outcomes profile compared to PTBD after failed ERCP, even in different medical insurance programs.